2020
DOI: 10.1126/sciadv.aaz9507
|View full text |Cite
|
Sign up to set email alerts
|

Climate models miss most of the coarse dust in the atmosphere

Abstract: Coarse mineral dust (diameter, ≥5 μm) is an important component of the Earth system that affects clouds, ocean ecosystems, and climate. Despite their significance, climate models consistently underestimate the amount of coarse dust in the atmosphere when compared to measurements. Here, we estimate the global load of coarse dust using a framework that leverages dozens of measurements of atmospheric dust size distributions. We find that the atmosphere contains 17 Tg of coarse dust, which is four times more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
207
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(231 citation statements)
references
References 80 publications
21
207
3
Order By: Relevance
“…The use of the volume averaging method to compute the bulk dust optical properties (e.g., complex refractive index) based on the dust mineral species probably overestimate absorption (Zhang et al, 2015;Li and Sokolik, 2018), leading to an artificial warming in CAM5 and CAM6. Our model very likely underestimates a large fraction of the coarse-mode dust particles (diameter >5 µm) according to a recent study (Adebiyi and Kok, 2020), and thus underestimates the dust warming effect. In addition, the transport of "giant" dust particles (diameter >20 µm) is still a representation issue that remains unsolved.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The use of the volume averaging method to compute the bulk dust optical properties (e.g., complex refractive index) based on the dust mineral species probably overestimate absorption (Zhang et al, 2015;Li and Sokolik, 2018), leading to an artificial warming in CAM5 and CAM6. Our model very likely underestimates a large fraction of the coarse-mode dust particles (diameter >5 µm) according to a recent study (Adebiyi and Kok, 2020), and thus underestimates the dust warming effect. In addition, the transport of "giant" dust particles (diameter >20 µm) is still a representation issue that remains unsolved.…”
Section: Discussionsupporting
confidence: 52%
“…There is also a strong warming contribution over desert land regions such as North Africa and the Middle East compared to remote regions due to a higher shortwave absorbing efficiency of large-sized particles (Kok et al, 2017) which are found at a relatively larger fraction close to the emission source (Mahowald et al, 2014;Ryder et al, 2019). These simulations underestimated coarse dust (diameter between 5-10 µm) and missed the very coarse dust (diameter >10 µm), as well underestimated transport of particles >5 µm in diameter further away from the source (Ryder et al, 2019;Adebiyi and Kok, 2020). This underestimation of the coarse and very coarse dust particle transport may result from inaccurately representing turbulent or convective vertical mixing that could decrease the dry deposition of dust aerosols (Adebiyi and Kok, 2020) and from not accounting for the dust asphericity which can increase the gravitational settling lifetime (Huang et al, 2020).…”
Section: Base Simulation Direct Radiative Effectmentioning
confidence: 96%
See 1 more Smart Citation
“…Dust forecasts incorporating the assimilation of satellitederived τ a can circumvent a difficulty global aerosol models encounter, in which τ a is too low further away from a source region (e.g., Kim et al, 2014;Evan et al, 2014;Ansmann et al, 2017). As such, the assimilation of observed τ a holds the promise of more accurate depictions of the global aerosol distribution.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The count median dry radius of each mode can vary between fixed boundaries at 6 nm, 60 nm and 1 µm. Super coarse mineral dust particles are therefore only included as part of the coarse modes with mean radius larger than 1 µm and their mass is probably underrepresented (Adebiyi and Kok, 2020). However, their role in the dust-pollutioncloud interactions is limited by their low number concentration, corresponding to a low probability for pollution particles to coagulate with them, and a comparably short atmospheric residence time, leaving less time for chemical ageing.…”
mentioning
confidence: 99%